Review of Odometer Method for Predicting Heave on the Expansive Soil - Willis Diana; Muntohar, Agus Setyo; Widianti, Anita (International Journal of Sustainable Construction Engineering and Technology, 2020)
In foundation design on an expansive soil, the most critical step is to quantify accurately the magnitude of heave and swelling pressure due to change in moisture content. The one-dimensional odometer has been widely accepted method to determine the heave and swelling pressure of expansive soil. Its simplicity, suitability, and the availability were the reasons for the frequent use of odometer swell testing technique, but many procedures were identified to measure the swelling properties. Each testing procedures were not unique and resulted different swelling properties and heave prediction. Then, this paper provides an overview of various existing heave prediction by odometer methods and evaluate common practices of this methods. The techniques were reviewed systematically and summarized. The study summarized a state-of-the-art heave prediction based on the odometer methods. Various equations forms to predict heave based on the odometer method have been presented, but the fundamental principles were the same to propose the equation of heave prediction. The differences in these methods were related to the procedures in which the heave index parameter were determined. The three main procedures of odometer test, i.e. consolidation swell (CS), constant volume CV, and swell overburden (SO), have been summarized. Most of the heave prediction uses the parameter from CS and CV methods. Several reports have shown that the closest estimates of field heave were predicted based on CV method.